1999
DOI: 10.1088/0953-8984/11/49/313
|View full text |Cite
|
Sign up to set email alerts
|

Electronic phenomena in nanodispersed thin films

Abstract: We review experimental data on the electron and photon emission from island metal films (IMFs) energized by passing current or by infrared laser irradiation. A model of nonequilibrium heating of the electron gas in nanoparticles is substantiated and used to interpret the experimental results. The applications of the island metal films are also exemplified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 38 publications
(58 reference statements)
3
18
0
Order By: Relevance
“…However, the light emission could be observed when V f is about 5.3 V, which is defined as turn-on voltage. Yamamoto et al [9] reported that 100 nA emission current could be obtained with device voltage of 14.8 V for PdO emission cathode, and for pure island Au/Ag films the emission current can be measured with more than 10 V device voltage [3][4][5][6]. With the over-layer of BaO, Ba, or organic molecular the metal island films could emit electrons with about 5 V device voltage.…”
Section: The Almentioning
confidence: 99%
See 1 more Smart Citation
“…However, the light emission could be observed when V f is about 5.3 V, which is defined as turn-on voltage. Yamamoto et al [9] reported that 100 nA emission current could be obtained with device voltage of 14.8 V for PdO emission cathode, and for pure island Au/Ag films the emission current can be measured with more than 10 V device voltage [3][4][5][6]. With the over-layer of BaO, Ba, or organic molecular the metal island films could emit electrons with about 5 V device voltage.…”
Section: The Almentioning
confidence: 99%
“…Strong electron emission was also obtained from patterned thin films of tin-indium oxide by Hartwell and Fonstad [2]. Electron emission from discontinuous thin metal films and semiconductor films was observed by some researchers [3][4][5][6]. Effect of low work function over-layer, such as BaO, organic molecular, on the electron emission properties were also researched [4,6].…”
Section: Introductionmentioning
confidence: 99%
“…The SCE was proposed by Elinson [1] in 1965 and developed by Hartwell and Fonstad [2] in 1975. In addition, the SCE cathodes of discontinuous thin metal films and semiconductor films have also been extensively investigated [3][4][5][6][7][8]. The effect of low performance on electron emission was also examined by Fedorovivh et al [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…There are two types of electron emitters, namely the single-layer film electron emitter and the double-layer film electron emitter. These two types of electron emitters both require the films to have a discontinuous structure [3][4][5][6][7][8]12,13]. For the single-layer film electron emitter, a discontinuous structure was obtained by adopting different deposition parameters [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Interest in technologies for fabrication and study of the physicochemical properties of nanosized structures made from transition metal oxides has grown significantly over the past decade, in connection with the search for new industrial applications. These structures, having electronic and hole conductivity at room temperature [1-3], sensor properties, photoconductivity, luminescence and absorption [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], are quite attractive for study. Important parameters of oxides include environmental friendliness, thermal stability and resistance to aging, and also low cost.…”
mentioning
confidence: 99%